2010
DOI: 10.1194/jlr.m001958
|View full text |Cite
|
Sign up to set email alerts
|

Berberine reduces methylation of the MTTP promoter and alleviates fatty liver induced by a high-fat diet in rats

Abstract: This article is available online at http://www.jlr.org Nonalcoholic fatty liver disease (NAFLD), characterized by excessive accumulation of triglyceride (TG) in the hepatocytes, affects from 10% to ‫ف‬ 39% of people worldwide ( 1, 2 ). It is closely associated with obesity ( 3 ), insulin resistance ( 4 ), and type 2 diabetes ( 5 ). We previously reported that in NAFLD patients without type 2 diabetes, up to 31.4% of individuals meet the criteria of metabolic syndrome, and 43.2% meet the criteria of impaired gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
101
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 38 publications
14
101
1
Order By: Relevance
“…1S). Similar to our results, liver Dnmt1 mRNA [11] and/or protein [53] was not affected by the HFD. In human skeletal muscle, mRNA levels of both DNMT3a and DNMT3b were not significantly changed by a short period of high-fat overfeeding [4].…”
Section: Discussionsupporting
confidence: 80%
“…1S). Similar to our results, liver Dnmt1 mRNA [11] and/or protein [53] was not affected by the HFD. In human skeletal muscle, mRNA levels of both DNMT3a and DNMT3b were not significantly changed by a short period of high-fat overfeeding [4].…”
Section: Discussionsupporting
confidence: 80%
“…The nutritional regulation on the epigenome during liver development is very limited. HF diets had been shown to mediate DNA methylation at specific CpG sites on the promoter of gene and affected gene expression, thereby leading to physiological alterations (4,7,10,11,18,29). A recent study that applied Illumina's Infinium Bead Array assessed at 27,578 CpG sites associated with 14,475 genes has shown that a short-term feeding of HF diet induced genome-wide DNA methylation change at CpG sites in the skeletal muscle of healthy young men (17).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbs have been traditionally used for treating liver disease worldwide (37), and there are numerous herbal products that are believed to benefit patients with NAFLD, with acceptable levels of safety. For example, previous studies have demonstrated that puerarin, baicalin and berberine, which are three major constituents of the Chinese herbs: Puerariae Radix, Scutellariae Radix and Coptidis Rhizoma, exhibit therapeutic effects on rats with NAFLD (20)(21)(22). However, there have been few reports regarding the compatibility of these constituents.…”
mentioning
confidence: 98%
“…1A-C), are three major constituents of the Chinese herbs: Puerariae Radix [roots of Pueraria lobata (Willd.) Ohwi, PR], Scutellariae Radix (roots of Scutellaria baicalensis Georgi SR) and Coptidis Rhizoma (rhizomes of Coptis chinensis Franch, CR), which have demonstrated therapeutic effects on rats models of NAFLD (20)(21)(22). It is believed that a combination of agents may effectively reduce side effects and improve adaptive resistance.…”
Section: Introductionmentioning
confidence: 99%